ITSBAT NIKAH POLIGAMI PERSPEKTIF UNDANG-UNDANG PERKAWINAN DAN SEMA NO. 3 TAHUN 2018 - Iffah Fathiah (Mawaddah: Jurnal Hukum Keluarga Islam, 2023)
Sirri marriage or marriage under the hand is something that has become very common in society. One of the factors influencing it is the principle that if the conditions and pillars of marriage have been fulfilled, then it is sufficient to carry out a marriage, including in polygamous marriages. This kind of marriage violates Article 2 paragraph (2) of the 1974 Marriage Law which requires the registration of every marriage. The necessity of marriage registration is not only for administrative order, but also to ensure legal certainty and protection for wives and children. Thus, the wife and children of a sirri marriage will lose legal certainty and protection because sirri marriages are not recognized by law. As a solution to the rise of sirri marriages, itsbat nikah is held so that the sirri marriages that have occurred are recorded and recognized by the state as regulated in article 7 of the Compilation of Islamic Law. Regarding the itsbat nikah of irri polygamy, it is still possible to be accepted and granted by the Religious Court based on the Decree of the Chairman of MARI Number KMA/032/SK/IV/200611 dated April 6, 2006 concerning the Application of Book II Guidelines for the Implementation of Court Duties and Administration. The rules contained in Book II contradict SEMA No. 3/2018 which states that the application for itsbat nikah polygamy on the basis of irri marriage cannot be accepted.